Cryptic species Anopheles daciae (Diptera: Culicidae) found in the Czech Republic and Slovakia - Blažejová, Hana; Šebesta, Oldřich; Rettich, František; Mendel, Jan; Čabanová, Viktória; Miterpáková, Martina; Betášová, Lenka; Peško, Juraj; Hubálek, Zdeněk; Kampen, Helge; Rudolf, Ivo (Parasitology research, 2018)
We report the distribution of mosquitoes of the maculipennis complex in two distinct areas of the Czech Republic (Bohemia and South Moravia) and in one locality of neighbouring Slovakia with emphasis on the detection of the newly described cryptic species Anopheles daciae (Linton, Nicolescu & Harbach, 2004). A total of 691 mosquitoes were analysed using a species-specific multiplex PCR assay to differentiate between the members of the maculipennis complex. In the Czech Republic, we found Anopheles maculipennis (with a prevalence rate of 1.4%), Anopheles messeae (49.0%) and Anopheles daciae (49.6%). In Slovakia, only An. messeae (52.1%) and An. daciae (47.9%) were detected. In this study, An. daciae was documented for the first time in the two countries where it represented a markedly higher proportion of maculipennis complex species (with an overall prevalence almost reaching 50%) in comparison to previous reports from Germany, Romania and Poland. The determination of the differential distribution of maculipennis complex species will contribute to assessing risks of mosquito-borne diseases such as malaria or dirofilariasis.
Keywords: Slovenská republika; Culicidae; Insect Vectors; Species Specificity; malárie; dirofilarióza; Female; Malaria; Animals; ženské pohlaví; Česká republika; hmyz - vektory; druhová specificita; Dirofilariasis; zvířata; Anopheles; Czech Republic; Slovakia